A rock physics modeling approach in analysis and integration of well logs and ultrasonic velocities for characterizing the reservoir facies of the Viola Limestone in southwestern Kansas - Cimino, Victor (Kansas State University, 2020)
Seismic facies analysis is the focus when utilizing seismic attributes in reservoir characterization, especially in cases of significant lithological and petrophysical heterogeneities. This project targets an understanding of lithofacies and petrophysical properties effects of the Viola Limestone carbonates with the aim of evaluating viability of seismic attributes in Viola reservoir-facies characterization, in Clark County, Kansas. To this end, this study integrates ultrasonic laboratory data, analysis of well-logs, and fluid replacement modeling. This study uses ultrasonic rock physics measurements to determine core elastic properties and how they relate to in situ values from well logs. Elastic moduli such as Poisson’s coefficient, Young’s modulus, Bulk modulus, and Shear modulus were calculated based on lab-measured ultrasonic values. These lab values were used along with in-situ well log values for Gassman’s fluid replacement modeling calculations to evaluate sensitivity of elastic properties to reservoir pore-fluid composition. These calculations were targeted in the known productive Viola B zone which is known for its hydrocarbon richness. Estimations from fluid replacement modeling were then used to compare producing Viola and non-producing Viola wells within the Morrison Northeast Field in Clark County, Kansas. Well to well evaluations using rock physics and lab tested data provide a deeper insight to well performance and hydrocarbon accumulation.
Keywords: Petroleum geology; Rock physics; Kansas; Geology; Gassmann's Fluid Replacement Modeling; Limestone reservoirs